Validity and Reliability of the Multidimensional Scale of Perceived Social Support (MSPSS) in Greek Secondary School Students - Vasiliki Efthymiou; George P. Chrousos; Kalliopi Kounenou; Antonios Kalamatianos; Christos Pezirkianidis; Markos Korelopoulos; Charikleia Stefanaki; Ntina Kourmousi (Children)
Background/Objectives: Resilience—a complex phenomenon embracing a number of factors on various levels—seems to be a most important skill to survive this vulnerable phase. One major factor is the perceived social support during adolescence. Recognizing gaps in perceived social support may lead to prevention of serious social and medical problems, including juvenile delinquency and stress-related diseases. Screening questionnaires to identify the gaps in perceived social support in Greek adolescents are lacking. The purpose of this study was to validate a Greek version of the Multidimensional Scale of Perceived Social Support (MSPSS), a self-report scale of perceived social support of the family, significant others, and friends. Methods: The MSPSS was translated into Greek and was administered to students of 15 to 18 years of age from several areas of Greece. Psychometric properties of the MSPSS tool were investigated by Exploratory Factor Analysis (EFA), using principal component analysis with the Varimax Rotation Method. For Confirmatory Factor Analysis (CFA), the Comparative Fit Index (CFI), Tucker–Lewis index (TLI), and the Root Mean Square Error of Approximation (RMSEA) were used. Results: A total of 999 students completed the MSPSS anonymously. The Greek version of the MSPSS scale exhibited large internal consistency (Cronbach’s α of 0.932, McDonald’s Omega of 0.926). Three of the factors explained 80.80% of total variance. Conclusions: The Greek adaptation of the MSPSS is a valid instrument, and professionals can apply it as a screening tool for perceived social support in adolescents.